Technological support in language learning and teaching - Didmanidze, Ibraim; Zoidze, Ketevan; Putkaradze, Nino (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
Technology in the classroom within educational centers is the present of education. The use of new technology in language learning has become the perfect complement in reaching proficiency and fluency, English or Georgian course accompanied by technological support are the most effective and attractive for students who want to be successful in their learning.This paper aims to highlight the role of using modern technology in teaching English or Georgian. It discusses different approaches and techniques which can assist English or Georgian languages learning students to improve their learning skills by using technology. Among these techniques are online English and Georgian languages learning web sites, computer assisted language learning programs, presentation software, electronic/on-line dictionaries, listening CD-players, and learning by watching and listening to videos/films.